2016
DOI: 10.1002/2015wr018414
|View full text |Cite
|
Sign up to set email alerts
|

On the value of surface saturated area dynamics mapped with thermal infrared imagery for modeling the hillslope-riparian-stream continuum

Abstract: The highly dynamic processes within a hillslope-riparian-stream (HRS) continuum are known to affect streamflow generation, but are yet not fully understood. Within this study, we simulated a headwater HRS continuum in western Luxembourg with an integrated hydrologic surface subsurface model (HydroGeoSphere). The model was setup with thorough consideration of catchment-specific attributes and we performed a multicriteria model evaluation (4 years) with special focus on the temporally varying spatial patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
156
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(164 citation statements)
references
References 105 publications
8
156
0
Order By: Relevance
“…We valid index of higher terrestrial and SUVA-254 rapidly increased. (Glaser et al, 2016;Klaus et al, 2015). was induced by terrestrial DOC input that eventually led to a For the days with diel fluctuations we reject our first hypothesis that the instream processes.…”
Section: Resultsmentioning
confidence: 39%
See 2 more Smart Citations
“…We valid index of higher terrestrial and SUVA-254 rapidly increased. (Glaser et al, 2016;Klaus et al, 2015). was induced by terrestrial DOC input that eventually led to a For the days with diel fluctuations we reject our first hypothesis that the instream processes.…”
Section: Resultsmentioning
confidence: 39%
“…For the combinations that included discharge, we generally observed weaker and more heterogeneous relationships (Figure 3 c,e,f and he Weierbach catchment, we are convinced that SUVAidentifying terrestrial DOC in diel DOC fluctuations. Several studies already demonstrated that SUVA (Catalán et al, 2013;Fasching et al, 2016;Lee et al, 2016;Weishaar et al catchment for rising SUVA-254 values serving as a valid index Immediately after rain events, discharge, DOC concentrations and SUVA surface or near-surface runoff processes (Glaser et al, 2016;Klaus et al, 2015) the increase in DOC concentrations was induced by terrestrial DOC input that s on processes controlling diel DOC fluctuations. For the days with diel fluctu generally observed both DOC and SUVA-254 maxima in the afternoon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, airborne and ground-based TIR imagery have been successfully used to describe longitudinal profiles of river temperature [27][28][29][30], to provide information on soil moisture and surface saturation patterns [31,32], to detect ground water exfiltration along the hillslope-riparian-stream continuum and inferring connectivity dynamics of water exfiltrating to the stream [33][34][35][36][37]. Furthermore, information obtained through TIR imagery has been used as a data source for hydrological model validation [32,38]. Thus far, the potential for handheld TIR imagery to assess water mixing dynamics in small streams has not been fully assessed [23,25,35,39], with the vast majority of the studies relying on airborne TIR observations or reporting only some marginal observations specifically on water mixing.…”
Section: Introductionmentioning
confidence: 99%
“…The Weierbach catchment shows a dynamic combination of fast and delayed rainfall-runoff reactions, thus high-frequency monitoring has the potential for capturing the entire range of runoff processes, the resulting runoff components and related (Glaser et al, 2016;Klaus et al, 2015;Martínez-Carreras et al, 2016a;Pfister et al, 2017;Schwab et al, 2016). 15 The DOC and nitrate concentrations in the Weierbach creek were measured in-situ with the UV-Vis spectrometer spectro::lyser (s::can Messtechnik GmbH).…”
Section: Introductionmentioning
confidence: 99%